The relationship between Pleurotus ostreatus and Aspergillus flavus and the production of aflatoxin - Ginterová, A; Polster, M; Janotková, O (Folia microbiologica, 1980)
The relationship between Pleurotus ostreatus and Aspergillus flavus in common mixed culture on various substrates was investiaged. It was found that P. Ostreatus, similarly to some other higher fungi, can liquidate colonies of A. flavus. This fungus does not produce aflatoxin and chromatographically similar compounds. On straw, corn cobs, millet and wheat A. flavus produced aflatoxin after a 3-week cultivation. A subsequent cultivation of P. ostreatus led to detoxication of straw and corn cobs but millet and wheat were not detoxicated. Cultivation of P. osteatus in the presence of 40-100 micrograms of aflatoxin B1 per g substrate did not result in detoxication of the material even after 34 d but the results showed that the aflatoxin concentration decreased to about one-fourth of the added amount.
Keywords: aflatoxiny; Aflatoxins; Aspergillus niger; Agaricales